A modified trajectory of kyphoplasty via superior pedicle notch for osteoporotic vertebral compression fractures: Technique note and clinical result - Jiang, Yi; Li, Jian; Yuan, Shuai; Zuo, Rujun; Liu, Chang; Zhang, Jiexun; Ma, Ming (Frontiers in Surgery, 2022)
Background. Percutaneous extra-pedicular kyphoplasty can achieve better clinical results than transpedicular kyphoplasty. However, lumbar segment artery injury as a disaster complication limits its clinical application. Objective. To describe and evaluate a modified trajectory of kyphoplasty for the treatment of osteoporotic vertebral compression fractures (OVCF). Methods. Eighty-one patients who underwent percutaneous kyphoplasty (PKP) for lumbar OVCF at our hospital between May 2017 and May 2021 were enrolled. The patients were divided into an observation group (via the superior pedicle approach) and a control group (via the transpedicular approach) according to the surgical trajectory. The surgical procedure was described in detail, and the imaging parameters were recorded. Preoperative and postoperative clinical data were collected for statistical analysis. Results. PKP via the superior pedicle notch approach could offer large abduction and cranial inclination angles without serious complications. The rate of paravertebral leakage was significantly lower in the observation group than in the control group. Surgery with a superior pedicle notch approach had a shorter operative time and fewer fluoroscopies. Conclusions. PKP via the superior pedicle notch approach is a modified extra-pedicular approach for lumbar osteoporotic vertebral compression fractures. This trajectory is an easy-to-use target position because it enters the vertebral body directly. A shorter operative time and lower radiation exposure can enhance recovery after surgery.